Diaphragmatic ultrasonography as a predictor for mechanical ventilation weaning in adults: an integrative review - Enathanael Ribeiro Soares; Joel Freires de Alencar Arrais; Flávio Vinicius Fagundes Xavier; Adalberto Veronese da Costa; Glêbia Alexa Cardoso; Wildberg Alencar Lima (Fisioterapia e Pesquisa)
ABSTRACT Diaphragmatic ultrasonography (US) has been used to evaluate several respiratory diseases. Due to portability, this examination can easily be performed at bedside, in wards, emergency rooms and especially in the intensive care unit To identify and analyze how diaphragmatic ultrasonography can support safe mechanical ventilation weaning based on scientific evidence. This is an integrative literature review. Bibliographic survey was conducted from September to November 2022 in the following electronic databases: SciELO, LILACS and PubMed. A total of eight articles were included and evaluated using the Newcastle-Ottawa and PEDro scales, showing intermediate to high methodological quality. In total, the studies included 482 adult volunteers, of both sexes, aged 58.09±8.03, who had undergone invasive mechanical ventilation for at least 24 hours and were under ventilation to continue invasive ventilation weaning. In the selected studies, we found three evaluative variables: diaphragmatic excursion (DE) (75%); diaphragmatic thickness (DT) (62.5%); and diaphragmatic thickening fraction (DTF) (100%). Incorporating DT, DE and DTF into protocols for mechanical ventilation weaning in critically ill patients seems to support decision-making on the ideal time for weaning, reducing extubation failure.